Diagnostic and Therapeutic Value of ERCP : Experience from a Tertiary Care Center - Pathak, Rahul; Lamsal, Manoj; Jha, Anurag; Kafle, Brindeswari; Hamal, Rabin (Journal of Institute of Medicine Nepal, 2024)
Introduction The role of ERCP to diagnose and manage biliopancreatic diseases is increasing since its inception with refinement of operator skill, technical advancement and better patient selection. The aim of the study was to explore common clinical and endoscopic characteristics, outcome, adverse events and safety profile of patients. Methods An observational study was conducted on patients undergoing ERCP in Department of Gastroenterology, Tribhuvan University Teaching Hospital, for management of biliopancreatic diseases from April 2023 to March 2024 after taking approval from IRC-IOM. Patient demographics, clinical characteristics, ERCP findings and post procedure outcome data were collected and analyzed using SPSS version 26. Results A total of 200 patients were included with mean age 52.36±17.04 years and female:male ratio of 3:2. Elective procedures were done in 182 (91%) patients and in 18 (9%) as urgent procedure (within 48 hours). The most common indications were choledocholithiasis (157, 78.5%) followed by benign biliary stricture (12, 6%). The most frequent papilla was type 1 papilla (normal variant) in 48% followed by type 3 papilla (protruding) in 30%. Difficult cannulation was encountered in 130 (51.5%) cases. Post ERCP pancreatitis (8, 4%) and hypoxia (9, 4.5%) were the most common procedure and anesthesia related adverse events respectively. Common therapeutic interventions included sphincterotomy (176, 88%), CBD stenting (154, 78.5%) and precut sphincterotomy (45, 22.5%). Conclusion ERCP was mostly done for benign diseases like CBD stone and benign biliary strictures. Common therapeutic procedures were sphincterotomy and CBD stenting. Complications related to procedure and anesthesia though occured, their rate was low.